A Deep-Rough Mutant of Campylobacter jejuni 81-176 Is Noninvasive for Intestinal Epithelial Cells - Kanipes, Margaret I. (American Society for Microbiology, 2004)
A waaF mutant of Campylobacter jejuni 81-176 showed decreased invasion of INT407 cells in vitro and increased sensitivity to some antibiotics compared to what was seen with the wild-type strain.